Informe de evaluación de cultivos y forrajeras en la estepa de La Pampa. Junio 2021 - Belmonte, María Laura; Cabo, Sergio Enrique; Lorda, Hector; Paredes, Silvia Susana; Pizarro, María José; Fuentes, Maria Elena (EEA Anguil, INTA, 2023)
EEA Anguil